GOS (Green Open Space) Video as an Educational Media for Students to Increase Knowledge and Awareness of Green Open Space - Eka Putri Azrai; Ade Suryanda; Bunga Widya Martin (LPPM Undiksha, 2025)
Increasing student’s knowledge and awareness of the existence of Green Open Space can be done through educational concepts. Educational videos are designed to make the process of students receiving information more enjoyable. This study aims to create a GOS (Green Open Space) video to increase students' knowledge and awareness of Green Open Spaces. The research method used is the Hannafin and Peck Research and Development (R&D) model. Data collection methods include questionnaires and tests. The data analysis used is quantitative analysis. The research subjects include material experts, media experts, linguists, grade X students, and Biology teachers. Experts' results of the validation and feasibility of the media obtained an average score of 92% with a very feasible category. The effectiveness test results for using the N-Gain value media (g more than 0.3) are in the medium-high category. This study concludes that the GOS (Green Open Space) video can be used as an educational medium for high school students to increase knowledge and awareness of Green Open Spaces. This study implies that the GOS (Green Open Space) video has been developed so that teachers can use it as a medium in learning material on handling environmental change.